2009
DOI: 10.1021/es802324j
|View full text |Cite
|
Sign up to set email alerts
|

Emissions Impacts and Benefits of Plug-In Hybrid Electric Vehicles and Vehicle-to-Grid Services

Abstract: Plug-in hybrid electric vehicles (PHEVs) have been promoted as a potential technology to reduce emissions of greenhouse gases and other pollutants by using electricity instead of petroleum, and byimproving electric system efficiency by providing vehicle-to-grid (V2G) services. We use an electric power system model to explicitly evaluate the change in generator dispatches resulting from PHEV deployment in the Texas grid, and apply fixed and non-parametric estimates of generator emissions rates, to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(133 citation statements)
references
References 14 publications
3
124
0
1
Order By: Relevance
“…Andersson et al (2010) find that providing regulating power with PIEV fleets in Germany and Sweden may be an economically viable strategy. Sioshansi and Denholm (2009) demonstrate that the provision of spinning reserves by electric vehicles could increase the efficiency of thermal electricity generation, which in turn decreases emissions. In a more general analysis, Sioshansi and Denholm (2010) analyze the value of plug-in hybrid electric vehicles as flexible grid resources, considering unit commitment and ramping constraints.…”
Section: Literaturementioning
confidence: 99%
“…Andersson et al (2010) find that providing regulating power with PIEV fleets in Germany and Sweden may be an economically viable strategy. Sioshansi and Denholm (2009) demonstrate that the provision of spinning reserves by electric vehicles could increase the efficiency of thermal electricity generation, which in turn decreases emissions. In a more general analysis, Sioshansi and Denholm (2010) analyze the value of plug-in hybrid electric vehicles as flexible grid resources, considering unit commitment and ramping constraints.…”
Section: Literaturementioning
confidence: 99%
“…While other dispatch models have been developed, the results are not spatially resolved and thus do not count for transmission constraints [53][54][55]. Very few studies are spatially resolved and amenable to air quality analyses [5,44,51].…”
Section: Ab32mentioning
confidence: 99%
“…A number of existing studies have found that plug-in hybrid electric vehicles (PHEVs) have emissions benefits over hybrid electric vehicles (HEV) and conventional vehicles even when accounting for grid emissions [1][2][3][4]. It has also been shown that the charge requirements of a conversion of a large portion of existing light duty auto fleets to PHEVs can be supported by existing grid infrastructure with minimal increases in annual energy demand [2,[5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important conclusions from prior studies is that emissions impacts of PHEVs are sensitive to the generation mix of a particular region [3,5]. While included as part of a previous study estimating percentages of light duty vehicle stock that could be supported by existing infrastructure in sub regions of the U.S. power grid [7], California has yet to be the subject of a comprehensive and detailed grid impact analysis covering emissions, operations, and the integration of a PHEV future.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation